THE LEGALITY OF THE BOARD OF DIRECTORS OF STATE-OWNED ENTERPRISES' CURRENT POSITIONS REGARDING PRICE FIXING AGREEMENT VIOLATIONS - Puteri Nurjanah; Elisatris Gultom; Anita Afriana (Cepalo, 2022)
The relationship between concurrent positions and price-fixing is explained in the Business Competition Supervisory Commission ("KPPU") Regulation Number 4 of 2011 regarding price-fixing behavior as regulated under Article 5 of Law Number 5 of 1999 will be efficiently conducted if competing companies have concurrent positions. This issue can potentially harm the business competition environment and severely impact the business situation in Indonesia. Although there are laws prohibiting concurrent positions, the practice of concurrent positions is still common, particularly for members of the Board of Directors ("BoD") in State-Owned Enterprises ("SOE"), which are supposed to manage public benefits and public welfare. The problems that will be discussed in this research are the legal certainty of the practice of concurrent positions by SOE directors and how the implications of the practice of concurrent positions of SOE directors on violation of price agreements in the case of increasing airfare prices. This study constitutes legal uncertainty regarding concurrent positions of the BoD in SOEs, and the Minister of SOE Regulation Number 3 of 2015 allows a member of the BoD of SOE to have concurrent positions. However, this contradicts the above regulations, which prohibit such practices. Therefore, there has been an inconsistency of norms between the Law and its implementing regulations, which violate the provisions in the higher hierarchy resulting in the practice of having concurrent positions that cause direct implications for the violation of the price-fixing agreement in the related case